1990
DOI: 10.1007/bf01951761
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 3β-hydroxycholest-5-en-26-oic acid in hamsters

Abstract: Metabolism of 26-hydroxycholesterol to 3 beta-hydroxychol-5-en-24-oic acid and other C24-bile acids has been expected to occur by way of 3 beta-hydroxycholest-5-en-26-oic acid in studies in vitro. 3 beta-Hydroxycholest-5-en-26-oic acid was infused intravenously into bile fistula hamsters and the following C24-bile acids were identified: 3 beta-hydroxychol-5-en-24-oic acid, lithocholic acid, chenodeoxycholic acid, and a small amount of cholic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…An alternative explanation for changes in the relative proportions of cholic acid and chenodeoxycholic or ,-muricholic acids can be the existence of another pathway in the formation of bile acids, in addition to the major pathway involving initial 7a-hydroxylation of cholesterol [10,30], as has been suggested by several investigators to occur in the rat, hamster, rabbit and man [11][12][13][14][15]31]. This route may involve initial 26-hydroxylation of cholesterol by mitochondria, leading predominantly to the formation of chenodeoxycholic acid and /3-muricholic acid [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for changes in the relative proportions of cholic acid and chenodeoxycholic or ,-muricholic acids can be the existence of another pathway in the formation of bile acids, in addition to the major pathway involving initial 7a-hydroxylation of cholesterol [10,30], as has been suggested by several investigators to occur in the rat, hamster, rabbit and man [11][12][13][14][15]31]. This route may involve initial 26-hydroxylation of cholesterol by mitochondria, leading predominantly to the formation of chenodeoxycholic acid and /3-muricholic acid [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of 27-hydroxycholesterol to rats, hamsters, rabbits and humans results in the formation of 7α-hydroxylated products [36][37][38]. Sterol 27-hydroxylase catalyzes the 27-hydroxylation of cholesterol, the first step in the acidic pathway [39] (Fig.…”
Section: Acidic or Alternative Pathwaymentioning
confidence: 99%
“…The inability of low inundations of 27-OH-C to interfere with LDL uptake and degradation could be explained by the observation that oxysterols can be metabolized by 7o-hydroxylase to form bile acids [22,29]. It can be speculated that 7a-hydroxylase maintains the expression of LDL receptors by metabolizing (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have suggested 27-hy droxycholesterol to be a likely candidate [l&22, 26,27]. 27-Hydroxycholesterol is synthesized from cholesterol by a cytochrome PhsO containing mitochondrial enzyme (C27-steroid 27-hydroxyla~) in most tissues [22,26,28], represents an intermediate in the synthesis of bile acids [22,29], is normally present in human plasma lipoprotein [22,30] and in healthy and athero~lero~~ human aorta [31,32]. Recently, Saucier et al [24], although not con&rmed by others [33], reported the presence of increased levels of oxysterols (24-, 25-and 27-hydroxycholesterol) and repression of HMG-CoA reductase in cholesterol fed-mice according to the hypothesis that intracellular oxysterols regulate the level of the reductase.…”
mentioning
confidence: 99%